How to draw bugs - Petty, Michelle; Kinnealy, Janice ([Mahwah, N.J.] : Troll, 1997)
Contains illustrated, step-by-step instructions for drawing caterpillars, butterflies, ants, ladybugs, centipedes, dragonflies, bumblebees, houseflies, mosquitoes, fireflies, spiders, crickets, and grasshoppers.
Young Adult
Young Adult
Keywords: Insects in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature; Insects in art; Drawing -- Technique; Insects in art; Drawing -- Technique